Spatial Variations in the Levels of Development in Uttar Pradesh - Ali, Alamtar (National Geographical Journal of India, 2022)
The present study aims to analyse the spatial patterns of selected fruitful indicators of development, i.e., female literacy, urbanization and non-agricultural rural workforce separately. To point out the spatial variations in the levels of development on the basis of development scores of selected output indicators, and to identify the levels of the degree of relationship between the indicators of development in the state of Uttar Pradesh. About fifty per cent districts of the study area experienced poor (low and very low) levels of development. The results of correlation matrix, that the indicators of development are the major determinants of high level of development in the state of Uttar Pradesh.